Aberrant methylation of suppressor of cytokine signalling-1 (SOCS-1) gene in pancreatic ductal neoplasms - Fukushima, N (Nature Publishing Group, 2003)
The suppressor of cytokine signalling-1 (SOCS-1) gene is frequently silenced in human hepatocellular carcinoma by aberrant methylation. The aim of this study was to determine if SOCS-1 is inactivated in pancreatic ductal neoplasms, and to investigate if aberrant methylation of this gene affected the Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway. Aberrant methylation in the CpG island of the SOCS-1 gene was detected in six of 19 (31.6%) human pancreatic cancer cell lines using methylation-specific PCR, and was associated with a loss or reduction of gene expression in five of the six methylated cell lines. Thirteen of 60 pancreatic ductal adenocarcinomas (21.7%) and two of 34 intraductal papillary mucinous neoplasms (IPMNs) (5.9%) had methylated SOCS-1. In contrast, SOCS-1 methylation was not seen in pancreatic normal ductal epithelia (zero out of 15), in pancreatic intraepithelial neoplasia (PanINs) (zero out of 49) or in the IPMNs without infiltrating cancer (zero out of 20). 5-Aza-2′-deoxycytidine treatment of the SOCS-1-methylated pancreatic cancer cell lines led to restoration of SOCS-1 gene expression. Interleukin-6, which has been shown to act through the JAK/STAT pathway to increase cell growth, induced modest time and dose-dependent cell proliferation in a SOCS-1-methylated cell line (PL10, P=0.015) but not in two unmethylated cell lines. These results indicate that loss of SOCS-1 gene is associated with transcriptional silencing and may have growth-promoting effects, and that its methylation is a useful marker of pancreatic cancer.